The institutionalisation of restorative justice in schools: a critical sensemaking account. Issue 2 (3rd May 2016) - Russell, Scott; Crocker, Diane
ABSTRACT: In this paper we use a case study to describe how one school successfully implemented restorative justice (RJ). We ask: how do teachers and administrators make sense of a shift from traditional discipline to RJ? How might their sensemaking process affect whether a shift toward RJ is sustainable? We answer these questions by drawing on critical sensemaking—a set of heuristics designed to map social-psychological processes underlying organisational change. Our findings affirm that RJ in schools cannot be mandated as a policy change or implemented through training in practices isolated from changes in organisational rules and formative context. In the language of critical sensemaking, implementing RJ as a programme or set of tools will not 'make sense' to teachers. In contrast, the approach at St Catherine's school leveraged specific sensemaking properties in a way that allowed the change process to become empowering, develop from the ground up and generate radical change in the school.